Understanding the effect of moisture on interfacial behaviors of geopolymer-aggregate interaction at molecular level. (3rd July 2023) - Tian, Zhongnan; Zhang, Zhengqi; Tang, Xiuming; Zhang, Yingnan; Gui, Zengjian; Tan, Junqing; Chang, Qingxi
Graphical abstract: Highlights: MD simulation can reveal the effect of moisture on interfacial behaviors of geopolymer-aggregate interaction; Wetting characteristics of aggregate surfaces were elucidated and compared. The interfacial mechanism of geopolymer-aggregate with the participation of moisture was explained. Mechanical behaviors of geopolymer-water-aggregate interface were investigated using peeling and shearing simulation. Abstract: The interaction between geopolymer and aggregate largely determines the mechanical properties and durability of the geopolymer concrete. The effects of moisture on interfacial behavior of geopolymer-aggregate interaction are poorly understood, especially at molecular level. Herein, molecular dynamics (MD) simulation was employed to reveal the interactive behaviors of geopolymer-aggregate interfacial system with the participation of moisture. Full atomistic models adopted for MD simulations were constructed using the sodium aluminum silicate hydrate ( N -ASH) gel model and the main chemical components of the aggregates, SiO2 and CaCO3 . Then the wetting characteristics of aggregate surfaces, interfacial characteristics and mechanical behaviors of the geopolymer-aggregate interfacial systems containing interfacial moisture were elucidated and compared. It is found that the SiO2 surface is hydrophobic while the CaCO3 surface exhibits hydrophilic characteristics. Interfacial moisture participates in electrostatic interaction, H-bond interaction and coordination interaction in geopolymer-aggregate interface area. Appropriate interfacial water is beneficial to the interfacial interaction of geopolymer-aggregate system, but excessive water will increase the risk of interfacial failure. The interfacial moisture affects the diffusion behavior of water molecules and Na + ions in geopolymer to the interfacial region, and the formation of H-bonds and coordination bonds at the interface. Mechanically, with the participation of interfacial moisture, the geopolymer-SiO2 interfacial system possesses stronger tensile strength, and a greater risk of shear failure than that of geopolymer-CaCO3 . The above atomic-level findings may facilitate a better design and fabrication of geopolymer concrete in engineering.